Lean Management: Review of Lean Consciousness for the Clinical Laboratory - Prakash, Praveen; Joshi, Arpita; Jahan, Aarzoo; Sharma, Santosh Kumar; Yadav, Shakti Kumar; Gupta, Ruchika; Singh, Harsh Vardhan; Sarin, Namrata; Singh, Sompal (Annals of Pathology and Laboratory Medicine, 2020)
Lean management is a work philosophy of continuous improvement to achieve a smooth work flow by minimizing all kinds of waste including time, cost and manpower. The concept of lean management started as early as 1980’s and was soon adopted by production industry. However, incorporation of this concept in healthcare has been very gradual and hesitant, though lean heath care has immense potential to improve operational performance. A clinical laboratory, which is essential in practice of evidence-based medicine, can be efficiently managed using lean management concept. Only a few publications in English literature have studied the effect of implementation of lean management in a clinical laboratory. There are certain challenges that a health care manager is likely to face in the implementation of lean management in clinical laboratory especially in developing nations. The present review discusses the implementation of lean management in a clinical laboratory with identification of various steps which require lean thinking.